The Relationship between Maternal Knowledge of Complementary Foods with the Nutritional Status of Toddlers - Naim, Hardianti; Mahendika, Devin; Afifah Harahap, Nur; Prabu Aji, Sulistyani; Batubara, Ardiana; Yunita, Lina; Pannyiwi, Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The results of data obtained from the Tangeban Inpatient Health Center of Masama District in the last three years, namely in 2015 showed that out of 269 toddlers, the prevalence of toddlers who weighed below normal was 32 people (11.9%), height below normal was 53 people (19.8%). In 2016, out of 489 under-fives, the prevalence of under-fives who weighed below normal was 73 people (14.9%), height below normal was 73 people (14.9%). Whereas in 2017 there were 493 toddlers, the prevalence of toddlers whose weight was below normal was 73 people (14.8%), height below normal was also 75 people (15.3%). From the target to be achieved by health workers Tangeban Inpatient Health Center Masama District is <1.0%. Or even 0%. The research design used is Analytical Observational Research, where the researcher only makes observations or observations of the research subject and looks for data related to the research without intervening in the variables to be studied. The type of research design used is Cross sectional design, namely by conducting data collection, measurement or observation of data on independent and dependent variables only once at one time at the same time. the number of samples used was 60 mothers of toddlers. The results of the study There is a relationship between maternal knowledge variables and children's nutritional status at Tangeban Health Center. This is evidenced from 41 respondents whose nutritional status is good, there are 33 respondents who have good knowledge and there are 8 respondents who have poor knowledge. While out of 19 people whose nutritional status is not good, there are 4 respondents who have good knowledge and there are 15 respondents whose nutritional knowledge is still classified as low or not good.